Noninvasive and continuous blood pressure monitoring with better accuracy by combining pulse arrival time and peak delay - Yibin Li; Shengnan Li; Ning Deng (International Journal of Distributed Sensor Networks, 2018)
In this article, we propose a more accurate method to achieve noninvasive and continuous blood pressure monitoring with the aid of pulse arrival time and peak delay. Theoretical analysis shows that peak delay is positively correlated with the viscoelastic delay. Analysis of 12 subjects indicates that pulse arrival time with the compensation of peak delay (PATC) is much steadier and more robust than traditional pulse arrival time. Three common models (linear, inverse linear, and inverse quadratic) are employed to study the relationship between pulse arrival time/PATC and blood pressure. From pulse arrival time to PATC, the average promotions of correlation coefficient for systolic blood pressure are 0.065, 0.060, and 0.058 for the three models, respectively, accounting for 8.59%, 7.68%, and 7.43% improvement; for diastolic blood pressure are 0.070, 0.067, and 0.064, respectively, accounting for 12.73%, 12.05%, and 11.48% improvement. Finally, we find that peak delay is efficacious against the negative effects of the terminal reflection and the viscoelastic delay on the peripheral pulse wave. Our method is promising in developing novel applications on portable and wearable device for real-time blood pressure monitoring.